Electromagnetic and Optical Pulse Propagation 2 Temporal Pulse Dynamics in Dispersive, Attenuative Media - Oughstun, Kurt E. (Springer Series in Optical Sciences,, 2009)
Electromagnetic and Optical Pulse Propagation presents a systematic treatment of the radiation and propagation of transient electromagnetic and optical wave fields (such as those used in ultrawideband radar and communications systems as well as in ultrashort pulsed optics) through causal, locally linear media which exhibit both temporal dispersion and absorption. Volume I presents a detailed, rigorous development of the fundamental theory of both time and frequency-domain electromagnetics, beginning with the classical Maxwell-Lorentz theory of microscopic electromagnetic fields and its invariance in the special theory of relativity, the correlation of the microscopic and macroscopic fields, and the angular spectrum representation of pulsed radiation fields in causally dispersive media. The theory provides a rigorous framework for applied research treating temporally pulsed wave fields in dielectric, conducting and semiconducting materials. Volume II presents the asymptotic description of specific pulsed wave fields in both Debye and Lorentz model dielectrics, Drude model conductors and composite model semiconductors.